2013
DOI: 10.1371/journal.pone.0060159
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Measurements of IgE-Mediated FcεRI Signaling Using an Integrated Microfluidic Platform

Abstract: Heterogeneity in responses of cells to a stimulus, such as a pathogen or allergen, can potentially play an important role in deciding the fate of the responding cell population and the overall systemic response. Measuring heterogeneous responses requires tools capable of interrogating individual cells. Cell signaling studies commonly do not have single-cell resolution because of the limitations of techniques used such as Westerns, ELISAs, mass spectrometry, and DNA microarrays. Microfluidics devices are increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…We can hypothesize that important housekeeping cellular mechanisms or biochemical processes might interfere with cellular effector functions, such as degranulation or chemokine production. In this line heterogeneity in the mast cell degranulatory response was reported by Liu et al 57 by using an integrated microfluidic platform. The authors suggested that heterogeneity might stem from cell-to-cell variability in the copy number of the tyrosine kinase Lyn.…”
Section: Discussionsupporting
confidence: 52%
“…We can hypothesize that important housekeeping cellular mechanisms or biochemical processes might interfere with cellular effector functions, such as degranulation or chemokine production. In this line heterogeneity in the mast cell degranulatory response was reported by Liu et al 57 by using an integrated microfluidic platform. The authors suggested that heterogeneity might stem from cell-to-cell variability in the copy number of the tyrosine kinase Lyn.…”
Section: Discussionsupporting
confidence: 52%
“…Mouse monoclonal anti-DNP-IgE was prepared as described by Liu et al . 37 . Trivalent ligand DF3 and FAM-conjugated DF3 were custom synthesized by AnaSpec Inc. (Fremont, CA).…”
Section: Methodsmentioning
confidence: 99%
“…We use the high-affinity IgE receptor, referred to as FcǫRI, model developed by Liu et al [43] to show the performance of algorithms on the large biological model. FcǫRI is a high-affinity receptor for the antigen-specific immunoglobulin E (IgE).…”
Section: Fcǫri Modelmentioning
confidence: 99%